Investigating the Speech Functions Used in Thewizardliz Youtube Videos and Its Implication in Speaking Skill Learning - Sabrina Aulia Hidayat (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2026)
Digital platforms have significantly expanded access to authentic English input, yet the pedagogical potential of speech functions in YouTube motivational monologues remains underexplored. This study investigates the types and distribution of speech functions in TheWizardLiz's YouTube videos and examines their implications for speaking skill development in EFL contexts. Employing a descriptive qualitative design, data were drawn from three purposively selected videos and supplemented by semi-structured interviews with four English Education students. Speech functions were classified using Holmes' (2013) framework and cross-referenced with Austin's (1962) and Searle's (1979) speech act theory. A total of 166 utterances were identified across four functional categories: directive (81; 48.8%), referential (41; 24.7%), expressive (36; 21.7%), and phatic (8; 4.8%). Metalinguistic and poetic functions were absent. The dominance of directive functions reflects the motivational genre's rhetorical goal of behavioral change. Pedagogically, exposure to these speech functions supports learners' pragmatic awareness, public speaking development, and communicative confidence. The study proposes concrete classroom applications including speech function identification tasks, imitation practice, and role-play activities grounded in Genre-Based Approaches.